Facial Features of Burmese with Past-Life Memories as Japanese soldiers - Ohkado, Masayuki (Journal of Scientific Exploration, 2014)
More than 2,600 cases of children with past-life memories have been found all over the world, and there are a number of cases in which a person's physical features corresponded with his/her past-life memories. These features included birthmarks, birth defects, physiques, postures, facial features, etc. This paper explores the possibility that in international cases, where subjects claim to have lived in foreign countries in their past lives, there can be a correlation between past-life memories and their current facial features. The subjects in the present study were Burmese who claimed to have past-life memories as Japanese soldiers during World War II. According to Ian Stevenson and Jürgen Keil, who investigated these cases, some of the subjects were said by Burmese people close to them to look more Japanese than Burmese. The present study investigated whether Japanese people judged facial pictures of these subjects as more Japanese-like than those of Burmese who claimed to have past-life memories as Burmese. Keywords: past-life memory-mind-body connection-facial feature-Japanese-Burmese <!–[if gte mso 9]> 0 0 1 165 943 chubu university 7 2 1106 14.0 <![endif]–> <!–[if gte mso 9]> Normal 0 10 pt 0 2 false false false EN-US JA X-NONE ([{£¥‘“〈《「『【〔＄（［｛｢￡￥ !%),.:;?]¢°’”‰′″℃、。々〉》」』】〕゛゜ゝゞ・ヽヾ！％），．：；？］｝｡｣､･ﾞﾟ￠ <![endif]–><!–[if gte mso 9]> <![endif]–> <!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:標準の表; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-parent:""; mso-padding-alt:0mm 5.4pt 0mm 5.4pt; mso-para-margin:0mm; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:Century; mso-ascii-font-family:Century; mso-ascii-theme-font:minor-latin; mso-hansi-font-family:Century; mso-hansi-theme-font:minor-latin; –> <!–[endif] –> <!–StartFragment–> <!–EndFragment–>